2000
DOI: 10.3354/dao043191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a virus obtained from snakeheads Ophicephalus striatus with epizootic ulcerative syndrome (EUS) in the Philippines

Abstract: This is the first report of the isolation and characterization of a fish virus from the Philippines. The virus was isolated using snakehead spleen cells (SHS) from severely lesioned epizootic ulcerative syndrome (EUS)-affected snakehead Ophicephalus striatus from Laguna de Bay, in January 1991. The virus induced cytopathic effects (CPE) in SHS cells yielding a titer of 3.02 × 10 6 TCID 50 ml -1 at 25°C within 2 to 3 d. Other susceptible cell lines included bluegill fry (BF-2), catfish spleen (CFS) and channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
10
1
1
Order By: Relevance
“…In previous studies on EUS, viral isolations used pooled tissues (Frerichs et al 1986, Lio-Po et al 2000. However, in the present study, the virus was recovered from all test organs, indicating that the EUS virus is not organ-specific.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In previous studies on EUS, viral isolations used pooled tissues (Frerichs et al 1986, Lio-Po et al 2000. However, in the present study, the virus was recovered from all test organs, indicating that the EUS virus is not organ-specific.…”
Section: Discussioncontrasting
confidence: 59%
“…The virus was found to be serologically related to the EUS rhabdovirus by neutralization tests using polyclonal antisera raised against the EUS rhabdovirus isolate, as described in a previous study (Lio-Po et al 2000). The overall success rate in viral isolations among experimental snakeheads in this study was 21%, although Fig.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The claims of different authors on association of various pathogenic microbes, e.g., bacteria (Chakraborty and Dastidar, 1991;Chakraborty et al, 1996;Mastan and Qureshi, 2001;Mukherjee et al, 1995;Rahman et al, 2002), virus (Frerichs, 1995;John et al, 2001;Lio-po et al, 2000), fungus (Lilley, 1999), etc., could not be established completely through histopathological, microbiological, and electron microscopical studies. A number of birnavirus, rhabdovirus, and reovirus have been isolated occasionally from fish affected by EUS in Southeast Asia, but it was suggested that the virus only represent adventitious infections unrelated to outbreak of EUS (Frerichs, 1992(Frerichs, , 1995.…”
Section: Introductionmentioning
confidence: 99%